Lichen secondary metabolites from the cultured lichen mycobionts of Teloschistes chrysophthalmus and Ramalina celastri and their antiviral activities - Fazio, A.T. (2007)
Lichens and spore-derived cultured mycobionts of Teloschistes chrysophthalmus and Ramalina celastri were studied chemically, and results indicated that they produced, respectively, parietin and usnic acid as major secondary metabolites, which were purified and identified. Identification of the compounds was performed by high performance liquid chromatography and structural elucidation by nuclear magnetic resonance ( 1 H) and electron impact mass spectrometry. Usnic acid exhibited antiviral activity whereas parietin had a virucidal effect against the arenaviruses Junín and Tacaribe. © 2007 Verlag der Zeitschrift für Naturforschung.